The Tattvasaṃgraha of Śāntarakṣita: selected metaphysical chapters - Śāntarakṣita 705-762 (Oxford University Press, 2021)
"The Tattvasaṃgraha, or Encyclopedia of Metaphysics, is the most influential and most frequently studied philosophical text from the late period of Indian Buddhism. This edition includes verses by Śāntarakṣita (c. 725-788 CE), which are clarified and expounded in the commentary of his student Kamalaśīla (c. 740-795 CE); both of these authors played crucial roles in founding the Buddhist tradition of Tibet. In the Tattvasaṃgraha, they explain, discuss and critique a vast range of views and arguments from across the whole South Asian philosophical and religious spectrum. The work deals at length with ideas drawn from Buddhism, Jainism, and a variety of traditions now incorporated within Hinduism, including Mīmāṃsā, Nyāya-vaiśeṣika, and Sāṃkhya; it also includes the earliest discussion of Advaita Vedānta in any Buddhist text. The chapters selected for translation from Sanskrit and Tibetan deal with such fundamental philosophical issues as the existence or nonexistence of God and the soul; the nature of matter and of causal relationships; the connection between words and their referents; the rules of logic; the sources of our knowledge; and the compatibility of beliefs about karma with Buddhism's fundamental claim that there is no self. Introductory chapters discuss translation choices and explain the forms of argument and methods of reasoning employed by Śāntarakṣita and Kamalaśīla"--